Static and dynamic analysis of laminated composite plates with integrated piezoelectrics - Thinh, Tran Ich; Ngoc, Le Kim (Vietnam Journal of Mechanics, 2008)
A Finite Element model based on First-order Shear Deformation Theory is developed for the static shape control and vibration control of la minated composite plates integrated with piezoelectric sensors and actuators. A nine-node isoparametric rectangular element with 45 degrees of freedom for the generalized displacements and 2 electrical degrees of freedom is implemented for the static and dynamic analyses. The model is validated by comparing with existing results documented in the literature. Some numerical results are presented. It is concluded that the shape of the piezoelectric laminated composite plates can reach the desired shape through passive control or active control. The influence of stacking sequence of composite plates and position of piezoelectric layers and sensors/actuators patches on the response of the piezoelectric composite plates is evaluated